IDENTIFIKASI DAMPAK DAN TINGKAT SERANGAN RAYAP TERHADAP BANGUNAN DI KABUPATEN KUANTAN SINGINGI - Rimba Kurniawan S; Rudianda Sulaeman; M. Mardhiansyah ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
This research aims to identifies of the impact and level of termite’s attack on the building in the district Kuantan Singingi. This research was conducted from February to March 2015 using quantitative descriptive method. The sample of this research is8villageswere taken from five subdistrict in Kuantan Singingi, in every village have been 10 houses were taken randomly, so the number of houses studied as many as 80 houses. Analysis of the datain this study using analytical techniques percentage .Based on the results of research showed that the rate of attacks Coptotermes reaches 33 unitsor 59%, Macrotermes gilvus reaches 17 unitsor 30%, and the least Cryptotermes reached 6unitsor 11%.Factorsthat influence the occurrence of termite’s attack in Kuantan Singingi, namely the factor of land, vegetation and the environment such as rainfall, humidity and temperature.Conditions environmental in Kuantan Singingi very suitable for life termites, high rainfall, maximum temperature range in Kuantan Singingi is 32.6°C-36.5°C and minimum temperatures ranging between 19.2°C-22°C, The maximum humidity between 94% -98%. The minimum humidity between 47% -57%. Rainfall between 94.20 to 445.3mm per year. Keywords: Termite, Level of attack , Building